2013
DOI: 10.4103/0019-5154.105279
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cutaneous drug reactions in patients visiting out patient departments of Indira Gandhi Government Medical College and Hospital (IGGMC and H), Nagpur

Abstract: Objectives:To detect cutaneous drug reactions through spontaneous reporting system in IGGMCand H, Nagpur and analyze them using standard assessment scales.Materials and Methods:An observational, prospective study was performed in patients attending dermatology OPD of IGGMC and H, Nagpur from 1st June 05 to 31st May 09. Patients were examined for cutaneous drug reactions (CDRs) by spontaneous Adverse Drug Reaction reporting system.Results:Among 2693 total ADRs reported, 872 (33.04%) were CDRs. Antimicrobials (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 3 publications
10
37
3
1
Order By: Relevance
“…This finding is less than that of 55.5%, 50.9% and 39.1% as reported by other groups. [18][19][20] It is approximately near (34.10%) to study done by Chatterjee. S, et al, and Ghosh.…”
Section: Miscellaneous Includesmentioning
confidence: 90%
See 2 more Smart Citations
“…This finding is less than that of 55.5%, 50.9% and 39.1% as reported by other groups. [18][19][20] It is approximately near (34.10%) to study done by Chatterjee. S, et al, and Ghosh.…”
Section: Miscellaneous Includesmentioning
confidence: 90%
“…Therefore, the frequency and proportions of dermatological ADRs from Indian System of Reporting cannot be matched (compared) with data from other reporting systems. 18,19,21 In this study, authors found out that, Oral and Injectable Antimicrobials (35%) are the leading cause of the dermatological ADRs. This finding is less than that of 55.5%, 50.9% and 39.1% as reported by other groups.…”
Section: Miscellaneous Includesmentioning
confidence: 99%
See 1 more Smart Citation
“…1,7,12 This patient developed allergic bronchial asthma & angioedema after taking one tablet of ibuprofen. He presented with swelling over lip, orbital area, throat and severe breathing difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Most common among them is cutaneous adverse drug reactions [1] with fixed drug eruption being the most common cutaneous drug reaction among the Indian population [2]. The drugs most commonly implicated in fixed drug eruption are analgesics and antibiotics [2].…”
Section: Introductionmentioning
confidence: 99%